1987
DOI: 10.1055/s-2007-1003502
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Disulfide Exchange by Thrombospondin

Abstract: Thrombospondin (TSP) forms sodium dodecyl sulfate (SDS)-stable complexes with thrombin and other proteases, apparently by thiol-disulfide ex change. It also forms complexes with other mole cules of TSP by a similar mechanism. TSP has a conformation-sensitive thiol and intrachain disul fide bond. Thus, TSP has the potential for covalently cross-linking itself and other proteins.In studies with labeled thrombin derivatized with a photoactivatable cross-linking reagent, Danishefsky and Detwiler 1 observed that af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 6 publications
3
14
0
Order By: Relevance
“…The first is that only a subpopulation of TSP-1 molecules in the correct conformation(s) (regardless of post-translational modifications) can participate in the activation process. In fact, it has been demonstrated that TSP-1 adopts markedly different conformations, depending on the temperature, pH, cation concentrations, and degree of purification[42][45]. Support for this hypothesis comes from evidence that the conformation of TSP-1 affects its efficiency in mediating thiol-disulfide exchange with other molecules[42][44], [46].…”
Section: Discussionmentioning
confidence: 99%
“…The first is that only a subpopulation of TSP-1 molecules in the correct conformation(s) (regardless of post-translational modifications) can participate in the activation process. In fact, it has been demonstrated that TSP-1 adopts markedly different conformations, depending on the temperature, pH, cation concentrations, and degree of purification[42][45]. Support for this hypothesis comes from evidence that the conformation of TSP-1 affects its efficiency in mediating thiol-disulfide exchange with other molecules[42][44], [46].…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal proximal TSR3 module contains an RGDA sequence, potentially allowing interactions of TSP1 with platelet integrins a IIb b 3 , a v b 3 and a 5 b 1 . The accessibility of the RGDA sequence and, therefore, the adhesive properties of TSP1 are thus tightly related to the Ca 2+ -ion concentration and disulfide bond matching [36,37]. Sun et al [38] have shown that controlled reduction of disulfide bonds in TSP1 by dithiothreitol increases its RGDA-dependent cell-adhesive properties.…”
Section: Structure and Functional Domains Of Tsp1mentioning
confidence: 99%
“…Free thiols and a Ca 2+ -modulated C-terminal region confer to TSP1 the capacity to form covalent bonds with other proteins, such as thrombin. TSP1 multimerization, due to disulfide bond exchange, has also been described [36]. More recently, protein disulfide isomerase (PDI) secreted by activated platelets was found to catalyze disulfide exchange reactions on the platelet surface [39].…”
Section: Structure and Functional Domains Of Tsp1mentioning
confidence: 99%
See 1 more Smart Citation
“…Upon release from activated platelets, TSP-1 binds back to the platelet surface in a Ca 2+ -dependent manner and is required for the secondary, secretion-dependent, phase of platelet aggregation (10). TSP-1 exists in multiple conformational states, some of which can interconvert reversibly, while others are restricted by covalent disulphide bonds (11). TSP-1 conformation varies in solution or is matrix-bound, reflecting the relative availability of TSP-1 domains to interact with different cellsurface receptors, which result in different functional properties (12).…”
mentioning
confidence: 99%